A study on MEMS vector hydrophone and its orientation algorithm. Issue 2 (31st March 2020) - Shang, Zhenzhen; Zhang, Wendong; Zhang, Guojun; Zhang, Xiaoyong; Zhang, Lansheng; Wang, Renxin
Abstract : Purpose: The problem of port and starboard ambiguity will exist when only utilize the vector or scalar parameters. Meanwhile, the amplitude-phase error between the vector and scalar can also cause this problem. In this paper, a compound MEMS vector hydrophone which contains cilia vector microstructure and piezoelectric ceramic tube has been presented to solve the problem. Compared with traditional MEMS vector hydrophone, the compound MEMS vector hydrophone can realize the measurement of sound pressure and vibration velocity simultaneously. Design/methodology/approach: A compound MEMS vector hydrophone has been presented. The unipolar directivity of the combined signal which combine the acoustic pressure and vibration velocity is used to achieve the direction of arrival (DOA). This paper introduced the working principle and the target detection mechanism of the compound vector hydrophone. The amplitude and phase error are analyzed and corrected in the standing wave tube. After that, the authors use beam-forming algorithm to estimate the DOA. Findings: The experimental results in the standing wave tube and the external field verified the vector hydrophone's directional accuracy up to 1 and 5 degrees, respectively. Practical implications: The research of compound vector hydrophone plays an important role in marine acoustic exploration and engineering applications. Originality/value: This research provides a basis for MEMS hydrophone directivity theory. The compound vector hydrophone has been applied in the underwater location, with a huge market potential in underwater detection systems.